A potter's workshop from Middle Bronze Age Cyprus: new light on production context, scale and variability. (1st June 2014) - Frankel, David; Webb, Jennifer M.
Abstract : When fire swept through a workshop at Ambelikou Aletri on Cyprus in the nineteenth or twentieth century BC it brought a sudden halt to pottery production, leaving the latest batch of recently fired vessels. The remains of the kiln and its immediate surroundings provide a rare opportunity to gain direct insight into the technology and organisation of a Middle Bronze Age pottery workshop in the eastern Mediterranean. Analysis of the batch of cutaway-mouthed jugs adjacent to the kiln reveals a level of standardisation focused more on vessel shape than capacity, and shows that at a detailed level, no two jugs were alike. This pottery production site provides vital background for the study of contemporary pottery assemblages on Cyprus and elsewhere in the broader region.